Exploring the Expansion, Equity and Excellence and Emergent Challenges in Higher Education in Nepal - Subedi, Govind (Perspectives on Higher Education, 2025)
The main aim of this article is to assess the current situation of higher education in Nepal, drawing on the mainly the secondary sources of data including UGC's EMIS Report. The main findings evolved as low GER (19) with having achieved the gender parity but wide disparity by provinces and caste/ethnicity of Nepal. Higher education is being provided through constituent, community and private campuses and the share of private providers is as high as 33 per cent of student-enrolment, and it especially manifests in applied and professional subjects. Excellence in higher education - world ranking, pass rates, capacity of teachers are found to be below the average. Some of the emerging challenges in higher education are the small size campuses, shrinking public expenditure on higher education, high exodus of 10+2 pass outs youngsters, huge youth labour migration, hidden process of privatisation and lop-sided intake in undergraduate programmes in the country.